2019
DOI: 10.1142/s101370251950001x
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ referral practice and related healthcare utilization for people with low back pain in Singapore: A retrospective study

Abstract: Background: Low back pain is a common musculoskeletal disorder that can incur high financial burden. A significant proportion of this burden may be incurred from referrals to health services and subsequent healthcare usages. Patients’ overall experience of pain and its related life interferences may also have some relevance to this usage. Objective: This study aimed to examine the referral practices and subsequent health service utilization of patients with LBP within a tertiary specialist clinic setting. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Among the indicators of use of healthcare services, physical therapy consultations offer the potential to explain the incapacity. However, in the present investigation, as corroborated through the investigations of Loy et al 54 and Freburger et al, 55 there was no association between consultations with a physiotherapist and occurrences of low back pain-related disability. It is possible that this result was influenced by the low number of participants who had physical therapy consultation during the preceding six weeks (only 3%), which would demonstrate flaws in the medical referral system within public services and health plan services in Brazil and problems regarding timely access.…”
Section: Discussionsupporting
confidence: 77%
“…Among the indicators of use of healthcare services, physical therapy consultations offer the potential to explain the incapacity. However, in the present investigation, as corroborated through the investigations of Loy et al 54 and Freburger et al, 55 there was no association between consultations with a physiotherapist and occurrences of low back pain-related disability. It is possible that this result was influenced by the low number of participants who had physical therapy consultation during the preceding six weeks (only 3%), which would demonstrate flaws in the medical referral system within public services and health plan services in Brazil and problems regarding timely access.…”
Section: Discussionsupporting
confidence: 77%
“…Ten ( n = 1) studies reported clinical features that influence imaging CDM (Barnett et al., 2020; Ely et al., 2018; Ferreira et al., 2019; Graves et al., 2012; Kohns et al., 2018; Loy et al., 2019; Peurois et al., 2022; Piccoliori et al., 2013; Schlemmer et al., 2015; Urrutia et al., 2020) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Ten (n = 1) studies reported clinical features that influence imaging CDM (Barnett et al, 2020;Ely et al, 2018;Ferreira et al, 2019;Graves et al, 2012;Kohns et al, 2018;Loy et al, 2019;Peurois et al, 2022;Piccoliori et al, 2013;Schlemmer et al, 2015;Urrutia et al, 2020) (Table 2). Clinical features were divided into seven subcategories: red flags (n = 4; 40%), pain (n = 6; 60%), neurological deficit (n = 3; 30%), cognitive and disability metrics (n = 3; 30%), presentation (n = 1; 10%) and injury severity (n = 1; 10%) (Table 2).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…While factors associated with medical healthcare and physical therapy utilization may be similar (e.g. source of referral, pain and disability) [ 23 ], it remains unknown whether disparities exist in terms of factors associated with physical therapy utilization versus overall medical utilization in pregnant and postpartum women due to the lack of direct access to physical therapy in some countries or locations (i.e. Taiwan) [ 24 ] and socio-cultural differences among countries [ 21 ].…”
Section: Introductionmentioning
confidence: 99%